Affald fra en glasproduktion ved Glargårde - Jouttijärvi, Arne (Hikuin, 2010)
Waste from a glasswork at Glargaarde in northern Jutland By Arne Jouttijärvi Waste found during archaeological investigation of a Renaissance glasswork by Glargaard in northern Jutland have been analyzed. Among the parts from the furnace clay plates that had been used for closing openings in the furnace was found (Fig. 1). Some of these were made from ordinary clay, while fireclay was used for another group. This probably reflects the use in different parts of the furnace or different furnaces. The crucibles for melting of the glass were also made from fireclay. As raw clay and unburned crucibles were found, it could be seen, that the crucibles were made at Glargårde from a mixture of fresh clay and grog made from old crucibles. Frit, the intermediate product of the glassmaking process, was identified as greyish half molten lumps (Fig. 3), having a composition close to that of the finished glass. Window glass was apparently the main product of the glasswork, and tree types of glass were identified (Fig. 7). The light olive-green glass normally associated with »forest glass« did constitute a large part of the glass fragments found, but the glassmaker at Glargårde had also been able to produce nearly colourless glass by decoloration with manganese oxide. A third type of glass was coloured bright green using copper oxide. This type was the only one used for the production of painted window panels. The paintings were primarily made in a brown color, using iron oxide as a pigment, mixed with lead containing glass. The lead-oxide probably made the fusing of the paint easier. A gray color on some glass fragments was identified as a copper oxide. On similar painted window fragments from Ribe to shades of brown was used, produces by the addition of different amounts of iron oxide to a pulverized lead glass.